2019
DOI: 10.14260/jemds/2019/776
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Pregnancy Complicated by Obstetric Cholestasis

Abstract: BACKGROUND Pruritus is the primary clinical symptom of ICP. It may considerably impair the patient's quality of life causing sleep deprivation, psychological suffering and even suicidal thoughts. Pruritus is most severe in the evening, with a predilection for the palms of the hands and soles of the feet, and is not associated with any specific skin lesions. The main biochemical alterations are elevations of serum bile acids and aminotransferase activities. We wanted to study the outcome of pregnancy complicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Similar studies reports preterm 13.09%, 10 10.67%. 13 The majority 52.5% had an APGAR score at one minute was 8, with a mean score and SD (6.58±0.45) however other study reports less than 7 at one in 18.39%. 10 The majority of 70.5% had a score of 9 at 5 minutes with a mean score of (7.79±0.65).…”
Section: Discussionmentioning
confidence: 76%
“…Similar studies reports preterm 13.09%, 10 10.67%. 13 The majority 52.5% had an APGAR score at one minute was 8, with a mean score and SD (6.58±0.45) however other study reports less than 7 at one in 18.39%. 10 The majority of 70.5% had a score of 9 at 5 minutes with a mean score of (7.79±0.65).…”
Section: Discussionmentioning
confidence: 76%
“…The overall rate of LSCS deliveries among pregnant women with ICP in the present study was similar to the findings reported in other investigations that focused solely on pregnant women with ICP but without FL. [24] reported LSCS rates of 44.5%, 46.81%, and 38.67%, respectively, in their studies. It is important to note that these studies exclusively included pregnant women with ICP without FL.…”
Section: Discussionmentioning
confidence: 91%